Special and Differential Treatment for Developing Countries - Emanuel Ornelas (Center for Economic Studies and ifo Institute (CESifo), 2016)
Special and Differential Treatment for Developing Countries (SDT) constitutes a central feature of the GATT/WTO system. Its formal goal is to foster export-led growth in developing countries. Its theoretical foundations and empirical support are, however, weak at best. In particular, SDT conflicts with the GATT's two key principles of reciprocity and nondiscrimination, compromising the efficiency of the multilateral trading system. Still, if SDT provisions help those who most need help, sacrificing economic efficiency may be justifiable. However, there are numerous criticisms, on theoretical and empirical grounds, to the premises and the achievements of SDT-based disciplines, casting serious doubt on its effectiveness in helping developing countries trade and grow. For researchers, the good news is that there is plenty of room for progress, with several important areas where our understanding remains unsatisfactory but progress is feasible–that is, where the expected return to research effort seems unusually high.
Keywords: F13; F55; F63; O19; O24; 330; generalized system of preferences; preferential tariffs; trade policy; World Trade Organization; terms of trade; firm delocation; export-led growth